Trust in the provider and accurate self-reported PrEP adherence among adolescent girls and young women in South Africa and Zimbabwe: HPTN 082 study - Geetha Beauchamp; Deborah Donnell; Sybil Hosek; Peter L. Anderson; Kwun C. G. Chan; Bonnie J. Dye; Nyaradzo Mgodi; Linda-Gail Bekker; Sinead Delany-Moretlwe; Connie Celum (BMC, 2023)
Abstract Background Trust is an important cornerstone of patient-provider communication. Accurate reporting of pre-exposure prophylaxis (PrEP) adherence is vital for providers to determine who needs adherence support, especially adolescent girls and young women (AGYW) disproportionately affected by newly diagnosed HIV. Methods This is a secondary analysis of the HPTN 082 open-label PrEP demonstration trial. From 2016-2018, 451 AGYW aged 16-25 years were enrolled in South Africa (Cape Town and Johannesburg) and Zimbabwe (Harare). PrEP was initiated by 427, and 354 (83%) had month three patient-reported adherence responses and intracellular tenofovir diphosphate (TFV-DP) measurements. The patient-reported adherence response to 'In the past month, how often did you take the tablet?' was dichotomized as 'high' if the response was every day or most days, and 'low' if some days or not many days or never. The biomarker marker evidence of adherence in dried blood spots was defined as 'high' if TFV-DP ≥ 700, and 'low' if < 350 fmol/punch. We used multinomial logistic regression to examine if trust in the PrEP provider was associated with concordance between patient-reported adherence and intracellular tenofovir-diphosphate (TFV-DP). Results AGYW who reported trust in their providers were almost four-fold (aOR 3.72, 95% CI 1.20-11.51) more likely to have concordant adherence (high self-reported adherence and high TFV-DP concentrations) compared to discordant non-adherence (high self-reported adherence and low TFV-DP concentrations). Conclusion Education and training of providers to build trusting relationships with AGYW may lead to more accurate reporting of PrEP adherence. With accurate reporting, adequate support can be provided to bolster adherence. Trial registration ClinicalTrials.gov Identifier: NCT02732730.